Efficacy and safety of RC48-ADC in HER2-positive and HER2-low metastatic breast cancer: a multicenter, real-world study - Qu, Fei; Lu, Rongrong; Wu, Xinyu; Liu, Qian; Zha, Mengyao; Li, Huihui; Yuan, Yuan; Han, Zhengxiang; Cai, Dongyan; Huang, Xiang; Yin, Yongmei; Li, Wei (Frontiers in Oncology, 2024)
BackgroundA standard treatment recommendation for third-line and subsequent treatments for advanced HER2-positive breast cancer is still missing, especially for low HER2 expression. Nevertheless, there is evidence that these patients might benefits from antibody-drug conjugates (ADCs) treatment. Therefore, this study aimed to evaluate the clinical efficacy, safety, and factors affecting efficacy of Disitamab Vedotin (RC48) for treating HER2-positive and HER2-low metastatic breast cancer (MBC) in the real-world setting.MethodsA retrospective study at five clinical sites was conducted in China, enrolling MBC patients treated with RC48 from July 01, 2021 and May 31, 2023. Patient demographics, treatment patterns, and adverse events (AEs) were recorded and analyzed.ResultsA total of 154 patients were included: 104 (67.53%) patients with HER2-positive and 50 (32.47%) patients with HER2-low MBC. The median progression-free survival (mPFS) was 5.06 months. The objective response rate (ORR) and disease control rate (DCR) were 36.36% and 68.83%, respectively. HER2-positive patients exhibited a mPFS of 5.93 and an ORR of 41.35%. In contrast, patients with low-HER2 had a mPFS of 4.28 months and an ORR of 26.00%. The most common AEs included neutropenia (54.55%), increased AST (53.25%), leukopenia (51.95%), and fatigue (43.51%), mostly graded mild to moderate (grade 1-2).ConclusionsThis extensive study in China demonstrated that RC48 has excellent therapeutic potential for both HER2-positive and HER2-low MBC with a favorable safety profile. The study also suggests that combination therapy significantly boosts efficacy beyond monotherapy, indicating a promising avenue for future ADC development.